PRE-STORAGE APPLICATION OF AQUEOUS OZONE, ALOE VERA GEL AND PACKAGING ON THE QUALITY AND STORABILITY OF ORANGE FRUITS - Sidiq Sidiq Kasnazany (Mesopotamia Journal of Agriculture)
This study aimed to determine the quality and storability of the orange fruit cv. Diyala after 60 days of storage at 6±1°C and 90% RH under aqueous ozone at 4 mg L-1 or 15% Aloe vera gel. The fruit packaging was applied in three types: without packing, perforated plastic bags, and paper wrapping bags. The experiment was performed in a complete randomized design with three replicates. These parameters were studied: weight loss, respiration rate, moisture content, firmness, pH, juice, total soluble solids, total titratable acidity, TSS/TA, total sugar, ascorbic acid, and total carotenoids. Results indicated that the lowest weight loss in orange fruits was recorded for the 15% Aloe vera + Perforated plastic bag (7.17%), the minimum respiration rate was recorded for the 15% Aloe vera + Perforated plastic bag (8.96 mg CO2 kg-1 h-1), the same treatment had the most significant effect on the moisture content (80.55%), all treatments significantly affected on the firmness of orange fruits. The aqueous ozone + Perforated plastic bag treatments were significantly superior to the control treatment on the pH value. On the other hand, the highest juice percentage was recorded from the control treatment—the total titratable acidity obtained in aqueous ozone + 15% Aloe vera (0.72%). Furthermore, 15% Aloe vera + without packaging significantly affected the ascorbic acid content of oranges. The aqueous ozone + 15% Aloe vera + fruit wrapping paper bag treatment greatly affected the total sugar and carotenoid contents.